2022
DOI: 10.29413/abs.2022-7.5-2.7
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a case of mixed infection with Lyme disease, tick-borne encephalitis and COVID-19

Abstract: Background. The relationship between pathogens of new diseases and tick-borne infections is an underinvestigated direction in the problem of infectious diseases.The aim. To show the features of identifying the markers of Borrelia burgdorferi, tickborne encephalitis and SARS-CoV-2 pathogens on the example of a case of a triple mixed infection (Lyme disease, tick-borne encephalitis and COVID-19) and using comprehensive studies.Methods. In 2019–2021, a comprehensive study of 7 blood samples from a patient with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…In the case under study, the previously unknown pathogen of the coinfection we identified in the tick microbiome received the opportunity for its replication and the appearance of specific antibodies in the patient, although its titer was low ( Figure 1 ). Earlier, for 2 years, we noted in one patient the clinical and diagnostic features of a mixed infection caused by TBEV, Borrelia , and SARS-CoV2 [ 28 ]. Using the indicators of antigen detection in ELISA, genetic markers in qPCR, and antibodies, as well as the degree of their avidity to these pathogens, we found that in the case of detection of three infections simultaneously, the bacterial pathogen B. burgdorferi dominates in the human body, causing a long-term chronic course of the disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case under study, the previously unknown pathogen of the coinfection we identified in the tick microbiome received the opportunity for its replication and the appearance of specific antibodies in the patient, although its titer was low ( Figure 1 ). Earlier, for 2 years, we noted in one patient the clinical and diagnostic features of a mixed infection caused by TBEV, Borrelia , and SARS-CoV2 [ 28 ]. Using the indicators of antigen detection in ELISA, genetic markers in qPCR, and antibodies, as well as the degree of their avidity to these pathogens, we found that in the case of detection of three infections simultaneously, the bacterial pathogen B. burgdorferi dominates in the human body, causing a long-term chronic course of the disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, we described a case of triple co-infection (TBEV + B. burgdorfery + SARS-Cov2), where we showed in the dynamics of observation for up to 2 years the predominance of not only the clinical symptoms of Lyme disease, but also the dominance of serological indicators for Borrelia spp. [20]. Due to the identification of high rates of infection of ticks with Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Сочетание ЭФ ИКБ с ЛФ КЭ чаще имело среднюю степень тяжести течения заболевания и клинически протекало с симптомами лихорадки и интоксикации, а при моноинфекции ЭФ ИКБ преобладали лёгкие случаи, что совпадало с полученными нами данными [1,3,6]. По-видимому, более тяжёлое течение смешанной инфекции по сравнению с моноинфекцией ИКБ чаще всего обусловлено преобладанием в клинической картине проявлений КЭ, хотя около 38 % обследованных нами больных с микстинфекцией имели лёгкое течение, которое клинически трудно отличить от моноинфекции ИКБ [8]. В периферической крови в начале заболевания у большинства больных КЭ и/или смешанной инфекцией ИКБ с КЭ выявляли снижение количества тромбоцитов, а также умеренное повышение СОЭ и числа нейтрофилов по сравнению с условно здоровым контролем [1,23].…”
Section: Discussionunclassified
“…В случае острого течения моноинфекции и микст-инфекции эритемной формы (ЭФ) ИКБ кольцевидная мигрирующая эритема является патогномоничным признаком заболевания, который, как правило, не требует серологической верификации. Вместе с тем поскольку, по данным литературы, к концу второй недели болезни иммуноглобулины (Ig) класса M к вирусу КЭ выявлялись у 63 %, а IgG к вирусу КЭ -только у 56 % пациентов микст-инфекцией ИКБ с КЭ, в начале развития сочетанного заболевания возможна гиподиагностика КЭ, приводящая к отсутствию своевременной противовирусной терапии [7,8].…”
Section: Clinical and Laboratory Prognostic Factors In Patients With ...unclassified